Pilkada Langsung dan Paradoks Desentralisasi: Ketidakseimbangan Antara Legitimasi Politik dan Kewenangan Pemerintahan Daerah di Indonesia - Ahmad Jumadil; Supeno Supeno; Nazifah Nazifah (Legalitas: Jurnal Hukum, 2026)
This study aims to examine how the method of selecting regional heads is inextricably linked to the design of decentralization within Indonesia's constitutional system. Debates regarding direct versus indirect regional head elections are often viewed merely through the lenses of democratic procedure, political efficiency, or local government stability. Yet, a deeper perspective—specifically, how authority is regulated and distributed between central and regional governments within the framework of autonomy—is frequently overlooked. This study explores the extent to which regional head election mechanisms truly align with decentralization principles, particularly from the perspective of asymmetric decentralization. Employing a normative legal approach, the study draws upon statutory regulations and conceptual frameworks. Primary legal sources consist of regulations concerning regional government and regional head elections, while secondary sources include relevant literature and prior research findings. The study reveals an imbalance: while directly elected regional heads possess strong political legitimacy, the actual authority exercised by regional governments remains limited due to a system that is still relatively centralized. This situation creates a paradox in the decentralization design: strong local political legitimacy exists alongside insufficient authority to manage regional governance. Consequently, the debate over regional head election mechanisms cannot be divorced from broader issues regarding decentralization design and the division of authority between the central and regional governments within Indonesia's constitutional system.